2016
DOI: 10.1089/lap.2015.0131
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Atlantic Telementoring with Pediatric Surgeons: Technical Considerations and Lessons Learned

Abstract: From this experience, several challenges were identified and addressed. Telementoring may be an effective means of improving adoption of new surgical techniques, ultimately improving patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…The use of social media outlets and live streaming has provided the ability for surgeons to collaborate on difficult cases and provide coaching between surgical teams from different continents. [43,44] Although steps are being taken to ease the translation of new research into the clinic, it is always going to be easier to utilize a surgeon's current skill-set than to require training in a new technique.…”
Section: Translation Of Technology To Surgeonsmentioning
confidence: 99%
“…The use of social media outlets and live streaming has provided the ability for surgeons to collaborate on difficult cases and provide coaching between surgical teams from different continents. [43,44] Although steps are being taken to ease the translation of new research into the clinic, it is always going to be easier to utilize a surgeon's current skill-set than to require training in a new technique.…”
Section: Translation Of Technology To Surgeonsmentioning
confidence: 99%
“…Preliminary studies conducted by Jarc et al (using the ghost tool platform with da Vinci surgical system) demonstrated effectiveness for both trainees and proctors during robot-assisted dry-lab training exercises, 7 and robot-assisted tissue dissection and suturing tasks on a live porcine model. 8 In both industry [9][10][11][12][13][14][15][16][17][18][19] and academia, [6][7][8][20][21][22][23][24][25][26][27] tele-mentoring solutions have been developed. These solutions facilitate transfer of information from a specialist surgeon to the operating surgeon via a communication channel and enables tele-mentoring during different types of surgeries.…”
mentioning
confidence: 99%
“…After removal of duplicates and screening of titles and abstracts, 157 full-text articles were assessed. A total of 66 studies were subsequently assessed as being suitable for inclusion 7-72 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%